THE EFFECT OF LEVERAGE, INVENTORY TURNOVER AND SALES GROWTH ON PROFIT GROWTH WITH FIRM SIZE AS MODERATING VARIABLES IN FOOD AND BEVERAGE COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE 2016 - 2021 - Uli Bastanta S, Citra; Fachrudin, Fachrudin; Satriawan, Bambang; Robin, Robin; Khaddafi, Muammar (CV. Radja Publika, 2022)
This study aims to examine the effect of Leverage, Inventory Turnover, and Sales Growth on Profit Growth with Firm Size as a moderating variable in Food and Beverage companies listed on the Indonesia Stock Exchange for the period 2016-2021. This study uses secondary data. This study uses a purposive sampling technique with a sample of 10 companies. The data analysis technique used is moderated regression analysis (MRA) with the help of the student version of SmartPLS 3.29. Based on the test results, it is known that the Leverage variable as measured by DER has a negative and insignificant effect on Profit Growth, with a significance value of 0.075 where the significance value of DER is greater than 0.05. Inventory Turnover has a positive and significant effect on Profit Growth, with a significance value of 0.038 where the ITO significance value is less than 0.05. Sales Growth has a positive and significant effect on Profit Growth, with a significance value of 0.000 where the significance value of SG is less than 0.05. Firm Size has a negative and significant effect on Profit Growth with a significance value of 0.023 where the significance value of FS is less than 0.05. Firm Size does not moderate the effect of DER on Profit Growth with a significance of 0.839 greater than 0.05. Firm Size does not moderate the effect of ITO on Profit Growth with a significance of 0.332 greater than 0.05. Firm Size does not moderate the effect of SG on Profit Growth with a significance of 0.223 greater than 0.05